Increased liver fat and glycogen stores after consumption of high versus low glycaemic index food: A randomized crossover study. Issue 1 (29th September 2016) - Bawden, Stephen; Stephenson, Mary; Falcone, Yirga; Lingaya, Melanie; Ciampi, Elisabetta; Hunter, Karl; Bligh, Frances; Schirra, Jörg; Taylor, Moira; Morris, Peter; Macdonald, Ian; Gowland, Penny; et al.
Abstract : Aim: To investigate the acute and longer‐term effects of low (LGI) versus high glycaemic index (HGI) diets on hepatic fat and glycogen accumulation and related blood measures in healthy volunteers. Methods: Eight healthy men (age 20.1 ± 0.4 years, body mass index 23.0 ± 0.9 kg/m 2 ) attended a test day before and after a 7‐day macronutrient‐ and energy‐matched HGI or LGI diet, followed by a minimum 4‐week wash‐out period, and then returned to repeat the intervention with the alternative diet. During test days, participants consumed either an HGI or an LGI test meal corresponding to their diet week, and liver fat [ 1 H magnetic resonance spectroscopy (MRS)], glycogen ( 13 C MRS) and gastric content volume (MRI) were measured. Blood samples were obtained regularly throughout the test day to assess plasma glucose and insulin levels. Results: Plasma glucose and insulin peak values and area under the curve were significantly greater after the HGI test meal compared with the LGI test meal, as expected. Hepatic glycogen concentrations increased more after the HGI test meal ( P < .05) and peak levels were significantly greater after 7 days of HGI dietary intervention compared with those at the beginning of the intervention ( P < .05). Liver fat fractions increased significantly after the HGI dietary intervention compared with the LGI dietary intervention (two‐way repeated‐measures analysis of variance P ≤ .05). Conclusions: Compared with an LGI diet, a 1‐week HGI diet increased hepatic fat and glycogen stores. This may have important clinical relevance for dietary interventions in the prevention and management of non‐alcoholic fatty liver disease.